ABSTRACT STUDY AND VALIDATION OF A DEVICE OF TESTS OF QUALITY CONTROL OF THE MECHANICAL CHARACTERISTICS OF TILES IN MICRO-CONCRETE - TOUKOUROU, ALPHONSE; AHOUANNOU, CLÉMENT; BOZABE, R. Karba; HOUNKONNOU, MAHOUTON NORBERT (My University, 2009)
The entitled work "abstract Study and validation of a device of tests of quality control of the mechanical characteristics of tiles, wide size in micro-concrete " has for main object to propose a technology of improvement of the tests of quality control of the mechanical characteristics such as: fold resistance three (3) points and four (4) points, shock resistance and traction resistance of the heel. For That purpose, an abstract study based on the NEWTON's 3rd law : " Principle of the action and the reaction " and the calculation of structures by the method of the finished elements allowed to model, to analyze and to size a new device which respects with a good rigor the recommendations and the requirements of the normative documents. This new device which groups the various tests of control of the mechanical characteristics mentioned above was conceived and validated by link of the results stemming from digital simulations by finished elements and from real tries.
Keywords: Micro-concrete; Tile; Device of the tests; The quality control; The characteristics mechanics; Action and reaction; Finished elements and Wide size.